Antibacterial sunscreen composite fabric and preparation method thereof

By using recycling linen fiber and chloride organic-inorganic composite material preparation of cooling antibacterial and regenerative fiber, combined with multiple composite powder and Sifit-pyrine season ammonium-salt-halide compounds, solve the antibacterial effect of the existing fabric And the lack of sunscreen performance, achieve efficient antibacterial, heat conduction, sunscreen and hydrophobic performance.

CN119329134AActive Publication Date: 2025-01-21WUHAN ZHOUCHI TECHNOLOGY & TRADE CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411448069.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-21
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The existing antibacterial functional composite fabrics are prone to weaken their antibacterial effects during wear and washing, and at the same time lack effective sun protection, especially under ultraviolet rays.

Method used

Recycling linen fiber and chloride organic-inorganic composite materials are used to prepare antibacterial and regenerative fiber, and the combination of multi-composite powder with Sifit-pyrine during ammonium salt-halide compounds is combined to form a high heating efficiency and antibacterial rate Fabric.

Benefits of technology

It achieves the long-lasting antibacterial effect, thermal conductivity and cooling performance of the fabric and good hydrophobic and antifouling properties. It also improves the sun protection performance and enhances the stability and durability of the antibacterial agent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119329134A_ABST
    Figure CN119329134A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of layered materials, and discloses an antibacterial sunscreen composite fabric and a preparation method thereof. The preparation method of the antibacterial sunscreen composite fabric comprises the following steps: preparing a spinning solution by taking recycled linen fibers and a chlorinated organic-inorganic composite material as raw materials, and spinning to obtain cool antibacterial regenerated fibers; blending cotton fibers and cool antibacterial regenerated fibers to obtain an inner layer; soaking the inner layer in the protective liquid, and after soaking is finished, pre-baking and baking to obtain a modified inner layer; blending the modified polyester fibers and the cool antibacterial regenerated fibers to obtain a surface layer; the surface layer is soaked in the hydrophobic finishing agent, and after soaking is finished, pre-baking and baking are conducted to obtain a modified surface layer; the modified inner layer and the modified surface layer are attached, stacked, aligned and compounded, and the antibacterial sunscreen composite fabric is obtained. The antibacterial sunscreen composite fabric disclosed by the invention has excellent lasting antibacterial property, sunscreen property and heat-conducting cool feeling effect, and also has hydrophobic antifouling property and wearing comfort.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of layered materials, in particular to an antibacterial sunscreen composite fabric and a preparation method thereof. Background Art

[0002] There are many varieties of textile fabrics. With the improvement of people's material living standards, the demand for textile fabrics is developing towards fashion, diversification and functionality. For example, after long-term use, fabrics are prone to breed a large number of bacteria or microorganisms, which will affect their practicality and safety. Therefore, antibacterial fabrics are becoming more and more popular.

[0003] For example, Chinese patent CN106515152B discloses a method for preparing a highly breathable and antibacterial functional composite fabric, which belongs to the technical field of textile fabrics. The present invention takes polyether diol and diisocyanate in a reactor for polymerization reaction, adds dimethylacetamide and stirs, and then reacts with ethylenediamine and cyclohexylamine to obtain a standby thermoplastic polyurethane elastomer, then takes polyester staple fiber, jade fiber, etc., mixes, sprays with an antibacterial aqueous solution and bakes, and then, after plying and spinning, the inner and outer layers are functional fabrics, and the middle layer is a thermoplastic polyurethane elastomer structure, and then hot-melt composite is obtained to obtain a highly breathable and antibacterial functional composite fabric. However, the antibacterial finishing agent is used for the inner and outer layers, and the antibacterial effect is easily weakened during wearing and washing. In addition, with the destruction of the ozone layer in recent years, the absorption and blocking ability of the ozone layer to short-wave ultraviolet rays has decreased. If human skin is exposed to ultraviolet rays for a long time, it may cause skin problems in the human body and increase the risk of skin cancer. Therefore, while solving the problem of durable antibacterial properties of fabrics, it is also crucial to improve the sunscreen performance of fabrics. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a method for preparing an antibacterial sunscreen composite fabric, comprising the following steps:

[0005] Step (1), using recycled flax fiber, 1-butyl-3-methylimidazole acetate, and chlorinated organic-inorganic composite material as raw materials to prepare spinning solution, spinning, and obtaining cool antibacterial regenerated fiber; wherein the preparation method of the chlorinated organic-inorganic composite material comprises the following steps:

[0006] Step B1, guanidine carbonate reacts with α-acetyl-γ-butyrolactone to obtain an intermediate product; the intermediate product reacts with acryloyl chloride to obtain an N-halamine compound precursor;

[0007] Step B2, 4-aminobutane-1-thiol reacts with 4-pyridinecarboxaldehyde to obtain a Schiff base-pyridine compound, which is then reacted with an N-halamine compound precursor, and finally subjected to a quaternization reaction to obtain a Schiff base-pyridine quaternary ammonium salt-halamine compound precursor;

[0008] Step B3, using boric acid and melamine as raw materials to prepare melamine diborate, coating the nano copper powder with melamine diborate, and then calcining to obtain modified copper powder; treating the modified copper powder to obtain amino modified copper powder;

[0009] The aminated modified copper powder and graphene oxide are assembled to obtain a multi-component composite powder; the multi-component composite powder is combined with a Schiff base-pyridine quaternary ammonium salt-halogenamine compound precursor using glutaraldehyde as a crosslinking agent to obtain an organic-inorganic composite material, which is then treated with sodium hypochlorite to obtain a chlorinated organic-inorganic composite material;

[0010] Step (2), blending cotton fiber and cool antibacterial regenerated fiber into yarn, knitting, and obtaining an inner layer; immersing the inner layer in a protective liquid, and after the immersion is completed, pre-baking and baking to obtain a modified inner layer;

[0011] Step (3), blending the modified polyester fiber and the cool antibacterial regenerated fiber into yarn, knitting, and obtaining a surface layer; immersing the surface layer in a hydrophobic finishing agent, and after the immersion is completed, pre-baking and baking to obtain a modified surface layer;

[0012] The modified inner layer and the modified surface layer are laminated, aligned and compounded to obtain an antibacterial and sun-proof composite fabric.

[0013] Preferably, in the step (1), the preparation method of the cool antibacterial regenerated fiber is as follows: the recycled flax fiber is mixed with 1-butyl-3-methylimidazole acetate, stirred at a speed of 500-600r / min for 1.5-2.5h in a constant temperature water bath at 75-85°C, dimethyl sulfoxide is added, stirring is continued for 2.5-3.5h, and then the chlorinated organic-inorganic composite material is added, stirred for 20-40min, degassed at 35-45°C for 10-15h to obtain a spinning solution, and spinning is performed; wherein, in the spinning solution, the mass ratio of the recycled flax fiber, 1-butyl-3-methylimidazole acetate, dimethyl sulfoxide, and the chlorinated organic-inorganic composite material is 1:(18-22):(54-66):(0.5-0.7).

[0014] Preferably, in step (1), the preparation method of the chlorinated organic-inorganic composite material is:

[0015] Step B1, guanidine carbonate, α-acetyl-γ-butyrolactone, triethylamine, and ethanol are mixed in a mass ratio of (11.3-22.6):(2.4-4.8):(3.8-7.6):(23-46), stirred at 28-32°C for 40-80min, then heated to 75-85°C, stirred for reaction for 20-30h to obtain a light yellow suspension, filtered, washed, and dried to obtain an intermediate product; the intermediate product is added with tetrahydrofuran Add triethylamine to furan, stir in an ice-water bath for 20-40 minutes, add acryloyl chloride, stir in an ice-water bath for 50-70 minutes, then stir at room temperature for 20-24 hours, filter, wash, and vacuum dry to obtain an N-halamine compound precursor; wherein the mass ratio of the intermediate product, tetrahydrofuran, triethylamine, and acryloyl chloride is (15-30):(150-250):(10.1-20.1):(9-18);

[0016] In the above process, guanidine carbonate and α-acetyl-γ-butyrolactone react to obtain an intermediate product; the hydroxyl group in the intermediate product reacts with the acyl chloride of acryloyl chloride to obtain an N-halamine compound precursor containing an amino group and a carbon-carbon double bond;

[0017] Step B2, adding 4-aminobutane-1-thiol to ethanol, ultrasonically treating for 20-40 min, then adding 4-pyridinecarboxaldehyde, stirring and reacting at 50-60° C. for 8-12 h, after the reaction is completed, removing the solvent by distillation under reduced pressure to obtain a Schiff base-pyridine compound; wherein the mass ratio of 4-aminobutane-1-thiol, ethanol, and 4-pyridinecarboxaldehyde is (10.5-21):(150-250):(10.7-21.4);

[0018] Add the N-halamine compound precursor to ethanol, perform ultrasonic treatment for 20-40 minutes, heat to 50-80°C, then add azobisisobutyronitrile and Schiff base-pyridine compound, stir and react for 3-5 hours, filter, wash and dry after the reaction to obtain Schiff base-pyridine-halamine compound precursor; wherein the mass ratio of N-halamine compound precursor, ethanol, azobisisobutyronitrile and Schiff base-pyridine compound is (11.2-22.4):(150-200):(0.2-0.5):(9.7-19.4);

[0019] Add dimethyl sulfoxide to a Schiff base-pyridine-halogenamine compound precursor and tetradecane bromide in a mass ratio of (10.2-20.2):(10.4-17.3):(150-250), react at 80-90° C. for 24-30 hours, filter, wash, and dry after the reaction to obtain a Schiff base-pyridine quaternary ammonium salt-halogenamine compound precursor;

[0020] In the above process, the amino group of 4-aminobutane-1-thiol reacts with the aldehyde group of 4-pyridinecarboxaldehyde to generate a Schiff base-pyridine compound; the thiol group in the Schiff base-pyridine compound reacts with the carbon-carbon double bond of the N-halamine compound precursor to generate a Schiff base-pyridine-halamine compound precursor; the Schiff base-pyridine-halamine compound precursor reacts with tetradecane bromide through a quaternization reaction to generate a Schiff base-pyridine quaternary ammonium salt-halamine compound precursor containing a long alkyl chain;

[0021] Step B3, mixing boric acid, melamine and deionized water in a mass ratio of (1.9-3.8):(2.5-4.5):(200-300), heating to 100-110° C. and stirring at a speed of 200-400 r / min for 7-9 hours, cooling naturally to room temperature, precipitating a crude product, filtering and drying to obtain melamine diborate;

[0022] Mixing nano copper powder, melamine diborate and deionized water in a mass ratio of (2-4):(0.2-0.4):(200-300), stirring at a speed of 150-250 r / min, heating at 240-260° C. until the deionized water is completely evaporated to obtain melamine diborate-coated copper powder, heating the melamine diborate-coated copper powder to 900-1100° C., maintaining the mixture in an argon and hydrogen flow for 2.5-3.5 hours to obtain modified copper powder, wherein the flow rate of argon is 200 sccm and the flow rate of hydrogen is 10 sccm;

[0023] The modified copper powder and 30wt% hydrogen peroxide aqueous solution are ultrasonically mixed at a mass ratio of 1:100 for 10-15h, and reacted at 105-110°C for 20-24h. After the reaction is completed, a hydroxylated modified copper powder is obtained. The hydroxylated modified copper powder, ethanol, and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane are mixed at a mass ratio of (15-20):(50-60):(1.5-2.5), and stirred at 60-70°C for 30-60min in a light-proof environment and a nitrogen atmosphere, and filtered, washed, and dried to obtain an amino-modified copper powder;

[0024] In the above process, melamine diborate generated by the reaction of boric acid and melamine is coated on the copper powder, and melamine diborate is used as a boron nitride precursor to in-situ grow nano-boron nitride on the copper powder to obtain modified copper powder, and the modified copper powder is then treated with N-(2-aminoethyl)-3-aminopropyltrimethoxysilane to introduce amino groups on the surface of the modified copper powder;

[0025] The aminated copper powder and the graphene oxide powder were ultrasonically dispersed in deionized water to obtain an aminated copper powder dispersion and a graphene oxide dispersion with a concentration of 2-5 mg / mL; the aminated copper powder dispersion was added dropwise to the graphene oxide dispersion at a speed of 1-2 mL / min, stirred at a speed of 400-600 r / min for 5-15 min, and then ultrasonically treated at a power of 150-250 W for 5-15 min, and then ultrasonically treated in an ice water bath at a pH of 7-8 and an ultrasonic power of 50-70 W for 10-20 min, centrifuged, removed the supernatant, and dried to obtain a multi-component composite powder;

[0026] The multi-component composite powder is mixed with ethanol containing 5 wt% glutaraldehyde in a dosage ratio of (2-4) g: (30-60) mL, reacted at 95-105° C. for 8-12 h, filtered, washed, and obtained a modified multi-component composite powder; the Schiff base-pyridine quaternary ammonium salt-halogenamine compound precursor, dimethyl sulfoxide, and the modified multi-component composite powder are mixed in a mass ratio of (5-10): (100-120): (3-5), stirred and reacted at 45-55° C. for 10-16 h, filtered, washed, and dried to obtain an organic-inorganic composite material;

[0027] The organic-inorganic composite material is added to a 10 wt % sodium hypochlorite aqueous solution at a solid-liquid ratio of 1:(25-35), and the pH is adjusted to 7 with acetic acid, stirred at room temperature for 1.5-2.5 hours, filtered, washed, and dried to obtain a chlorinated organic-inorganic composite material;

[0028] In the above process, the aminated copper powder and the graphene oxide powder are self-assembled through hydrogen bonding and electrostatic interaction between amino groups and carboxyl groups, and the aminated copper powder is deposited on the graphene oxide nanoparticles to form a multi-component composite powder; glutaraldehyde is used as a cross-linking agent to react with the Schiff base-pyridine quaternary ammonium salt-halamine compound precursor and the amino group of the multi-component composite powder, and the Schiff base-pyridine quaternary ammonium salt-halamine compound precursor is grafted on the multi-component composite powder, and more Schiff base structures are introduced to obtain an organic-inorganic composite material; further, the organic-inorganic composite material is chlorinated with sodium hypochlorite, and the -NH of the N-halamine compound precursor in the Schiff base-pyridine quaternary ammonium salt-halamine compound precursor on the surface of the organic-inorganic composite material is converted into -NCl;

[0029] Preferably, in step (2), the mass ratio of the cotton fiber to the cool antibacterial regenerated fiber is (60-70):(30-40), the English count of the blended yarn is 40-60S; the gram weight of the inner layer is 80-100g / m 2 The protective liquid is obtained by mixing polydimethylsiloxane, cyclohexane and dual-doped carbon dots in a mass ratio of (8-12):(88-92):(0.5-2).

[0030] Preferably, in the step (2), the immersion conditions are: immersion at room temperature for 20-30 minutes, immersion and rolling, the rolling rate is 90-95%, and the bath ratio is 1:(15-25).

[0031] Preferably, in step (3), the mass ratio of the modified polyester fiber to the cool antibacterial regenerated fiber is (75-85):(15-25), the English count of the blended yarn is 60-80S; the gram weight of the surface layer is 100-120g / m 2 ; The hydrophobic finishing agent is obtained by mixing polydimethylsiloxane and isopropyl alcohol in a volume ratio of 10:25.

[0032] Preferably, in step (3), the immersion conditions are: immersion at room temperature for 20-30 minutes, immersion and rolling, the rolling rate is 75-88%, and the bath ratio is 1:(15-25).

[0033] Preferably, in step (3), the method for preparing the modified polyester fiber comprises the following steps:

[0034] Step A1, wash freshly picked guava leaves with water and then dry them, grind them to obtain guava leaf powder, mix the guava leaf powder with deionized water, boil them at 90-95°C for 4.5-5.5h, filter them, heat them at 65-75°C to concentrate the filtrate to 5-10mL, add manganese sulfate monohydrate and titanium dioxide nanoparticles, keep them at 180-190°C for 5-6h, filter them, and dry them to obtain dual-doped carbon dots; wherein the mass ratio of guava leaf powder, deionized water, manganese sulfate monohydrate, and titanium dioxide nanoparticles is (15-20):(60-80):(0.03-0.06):(0.05-0.08);

[0035] The dual-doped carbon dots, activated polyester fibers, p-toluenesulfonic acid, and cyclohexane are mixed in a mass ratio of (1-2): (10-15): (0.1-0.2): (150-200), stirred and reacted at 120-140° C. for 3-5 hours in a nitrogen atmosphere, and after the reaction is completed, filtered, washed, and dried to obtain a surface-modified polyester fiber;

[0036] In the above process, guava leaf powder, manganese sulfate monohydrate, and titanium dioxide nanoparticles are used as raw materials to prepare carbon dots doped with manganese and nano-titanium dioxide, and the carboxyl groups on the surface of the activated polyester fiber react with the hydroxyl groups of the doped carbon dots to undergo an esterification reaction, so that the doped carbon dots are grafted onto the polyester fiber by forming chemical bonds;

[0037] Step A2, 3-aminopropyltriethoxysilane and ethanol are mixed in a dosage ratio of (8-16) g: (20-50) mL, and acetic acid is added to adjust the pH to 3.8-4.2 to obtain a mixed solution; the surface-modified polyester fiber is added to the mixed solution in a solid-liquid ratio of 1: (15-25), immersed at 65-75° C. for 40-80 min, taken out, washed, and dried to obtain an amino-modified polyester fiber;

[0038] Protocatechuic aldehyde is added to deionized water to dissolve to obtain a treatment solution with a concentration of 5-8 mg / mL, and the amino-modified polyester fiber is first added to the above treatment solution at a solid-liquid ratio of 1:(10-20), stirred at 45-55°C for 10-15 hours, taken out, dried at 55-65°C for 50-70 minutes, and washed to obtain protocatechuic aldehyde-modified polyester fiber; at 75-85°C, the protocatechuic aldehyde-modified polyester fiber is soaked in a 0.2 mol / L ferric chloride aqueous solution at a solid-liquid ratio of 1:(10-20) and a treatment time of 1-2 hours, taken out, dried at 55-65°C for 50-70 minutes, washed, and dried to obtain a modified polyester fiber;

[0039] In the above process, 3-aminopropyltriethoxysilane is hydrolyzed to generate silanol bonds which react with the surface-modified polyester fiber, thereby introducing amino groups on the surface-modified polyester fiber to obtain amino-modified polyester fiber; the amino groups of the amino-modified polyester fiber react with the aldehyde groups of protocatechuic aldehyde to introduce catechol structures on the surface of the polyester fiber; further, the phenolic hydroxyl groups in the catechol structures chelate with the iron ions in the ferric chloride to form modified polyester fiber;

[0040] Furthermore, in the step (3), the preparation method of the activated polyester fiber comprises: immersing the polyester fiber in a sodium hydroxide aqueous solution with a concentration of 20 g / L, alkali immersion treatment at 90-100° C. for 20-40 min, transferring the polyester fiber into a deionized water mixture of choline chloride and oxalic acid, deep treatment at 40-80° C. for 0.5-2 h, washing, and drying to obtain the activated polyester fiber, wherein the mass ratio of choline chloride to oxalic acid in the deionized water mixture of choline chloride and oxalic acid is 3:2, the total concentration of choline chloride and oxalic acid is 50 g / L, and the bath ratios of the alkali immersion treatment and the deep treatment are both (25-35):1;

[0041] In the above process, abundant hydroxyl and carboxyl groups are generated on the surface of the polyester fiber after activation treatment.

[0042] The antibacterial and sun-proof composite fabric is prepared by the method for preparing the antibacterial and sun-proof composite fabric.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] 1. The present invention uses recycled flax fiber as raw material to prepare cool antibacterial regenerated fiber, avoids the waste of natural fiber, and uses ionic liquid to dissolve cellulose, which has the advantages of good solubility, recyclability and environmental protection.

[0045] 2. The present invention obtains modified copper powder by in-situ growing nano boron nitride on copper powder. The boron nitride coating prevents oxidation of the nano copper powder, so that it maintains stable antibacterial properties. The modified copper powder has better thermal conductivity than copper powder. The modified copper powder is then deposited on graphene oxide nanosheets with thermal conductivity and antibacterial properties through self-assembly to form a heat conduction channel with "points and surfaces", which is conducive to establishing a heat conduction path and obtaining a multi-component composite powder with high thermal conductivity efficiency and antibacterial rate; further, the multi-component composite powder is combined with a Schiff base-pyridine quaternary ammonium salt-halogenamine compound precursor and then chlorinated to obtain a chlorinated organic-inorganic composite material. The inorganic multi-component composite powder is organically grafted to improve the interface effect between the multi-component composite powder and cellulose, so that the chlorinated organic- The inorganic composite material forms hydrogen bonds with the surface of cellulose, and the pyridinium quaternary ammonium salt, N-halamine and Schiff base in the chlorinated organic-inorganic composite material have complementary synergistic effects. The quaternary ammonium salt attracts bacteria to the N-halamine site through electrostatic attraction and quickly kills the bacteria, thereby effectively improving its antibacterial activity. The presence of the Schiff base structure can effectively improve the stability and durability of the antibacterial agent and enhance the antibacterial and antioxidant activities of the quaternary ammonium salt. Therefore, the chlorinated organic-inorganic composite material of the present invention is spun with recycled flax fiber to obtain a cool antibacterial regenerated fiber with a lasting antibacterial effect and a heat-conducting cool effect. In addition, the long alkyl chain in the Schiff base-pyridinium quaternary ammonium salt-halamine compound gives the cool antibacterial regenerated fiber good hydrophobicity and softness.

[0046] 3. The present invention uses guava leaves as raw materials to prepare dual-doped carbon dots doped with nano-titanium dioxide and manganese. The doping of nano-titanium dioxide and manganese improves the antibacterial effect of the carbon dots by promoting the generation of active oxygen, and the doping of nano-titanium dioxide can improve the ultraviolet shielding efficiency of the carbon dots. The dual-doped carbon dots are grafted onto polyester fibers to obtain surface-modified polyester fibers, which can improve the antibacterial and sunscreen properties of the polyester fibers. Furthermore, protocatechuic aldehyde is introduced into the surface-modified polyester fibers and iron ions are chelated. The protocatechuic aldehyde structure has good antibacterial and ultraviolet absorption capabilities due to its own benzene ring and phenolic hydroxyl groups. The chelation of iron ions can enhance bacterial adsorption and improve the antibacterial effect on the one hand, and on the other hand, iron ions can increase the reflection and scattering of ultraviolet rays on the surface of the polyester fibers and improve the sunscreen effect. Therefore, the modified polyester fiber of the present invention has permanent, antibacterial and sunscreen properties.

[0047] 4. Cotton fiber and cool antibacterial regenerated fiber are blended to obtain an inner layer, and the inner layer is immersed in a protective liquid composed of polydimethylsiloxane, cyclohexane, and dual-doped carbon dots, which can give the inner layer better hydrophobicity, softness and antibacterial and sunscreen effects; modified polyester fiber and cool antibacterial regenerated fiber are blended to obtain a surface layer, and the surface layer is immersed in a hydrophobic finishing agent, which can give the surface layer better hydrophobicity and softness. Therefore, the antibacterial and sunscreen composite fabric of the present invention not only has excellent long-lasting antibacterial properties, sunscreen properties and thermal conductivity and cool effects, but also has hydrophobicity and antifouling properties and wearing comfort. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 It is a process flow chart of the preparation method of the antibacterial sunscreen composite fabric of the present invention;

[0049] Figure 2 Schematic diagram of the synthesis of the N-halamine compound precursor of the present invention;

[0050] Figure 3 It is a schematic diagram of the synthesis of the Schiff base-pyridine quaternary ammonium salt-halamine compound precursor of the present invention;

[0051] Figure 4 It is a comparison chart of the antibacterial rate test of the antibacterial sunscreen composite fabrics of Examples 3-5 of the present invention and Comparative Examples 7-13;

[0052] Figure 5 It is a UPF test comparison chart of the antibacterial sunscreen composite fabrics of Examples 3-5 of the present invention and Comparative Examples 7-13;

[0053] Figure 6 It is a comparison chart of the contact coolness coefficient test of the antibacterial sunscreen composite fabrics of Examples 3-5 of the present invention and Comparative Examples 7-13. DETAILED DESCRIPTION

[0054] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0055] Example 1

[0056] This embodiment discloses a method for preparing a modified polyester fiber, comprising the following steps:

[0057] Step A1, wash the freshly picked guava leaves with water and dry them, grind them to obtain guava leaf powder, mix 17.5g of guava leaf powder with 70g of deionized water, cook at 93°C for 5h, filter, heat at 70°C to concentrate the filtrate to 7.5mL, add 0.04g of manganese sulfate monohydrate and 0.07g of titanium dioxide nanoparticles, keep at 185°C for 5.5h, filter, and dry to obtain dual-doped carbon dots;

[0058] The polyester fiber is immersed in a sodium hydroxide aqueous solution with a concentration of 20 g / L, and after alkali immersion treatment at 95°C for 30 minutes, it is transferred into a deionized water mixture of choline chloride and oxalic acid, and deep-treated at 60°C for 1 hour, washed, and dried to obtain an activated polyester fiber, wherein the mass ratio of choline chloride to oxalic acid in the deionized water mixture of choline chloride and oxalic acid is 3:2, the total concentration of choline chloride and oxalic acid is 50 g / L, and the bath ratios of the alkali immersion treatment and the deep treatment are both 30:1;

[0059] 1.5 g of dual-doped carbon dots, 12.5 g of activated polyester fiber, 0.15 g of p-toluenesulfonic acid, and 180 g of cyclohexane were mixed, stirred and reacted at 130 ° C for 4 h in a nitrogen atmosphere. After the reaction, the mixture was filtered, washed, and dried to obtain a surface-modified polyester fiber;

[0060] Step A2, 3-aminopropyltriethoxysilane and ethanol are mixed in a dosage ratio of 12 g:35 mL, and acetic acid is added to adjust the pH to 4 to obtain a mixed solution; the surface-modified polyester fiber is added to the mixed solution at a solid-liquid ratio of 1:20, immersed at 70° C. for 60 min, taken out, washed, and dried to obtain an amino-modified polyester fiber;

[0061] Protocatechuic aldehyde was added into deionized water to dissolve to obtain a treatment solution with a concentration of 6.5 mg / mL. The amino-modified polyester fiber was first added into the above treatment solution at a solid-liquid ratio of 1:15, stirred at 50°C for 12.5 hours, taken out, dried at 60°C for 60 minutes, washed, and obtained protocatechuic aldehyde-modified polyester fiber; at 80°C, the protocatechuic aldehyde-modified polyester fiber was immersed in a 0.2 mol / L ferric chloride aqueous solution with a solid-liquid ratio of 1:15 and a treatment time of 1.5 hours, taken out, dried at 60°C for 60 minutes, washed, and dried to obtain a modified polyester fiber.

[0062] Example 2

[0063] This embodiment discloses a method for preparing a chlorinated organic-inorganic composite material, comprising the following steps:

[0064] Step B1, 17g of guanidine carbonate, 3.6g of α-acetyl-γ-butyrolactone, 5.7g of triethylamine, and 34.5g of ethanol were stirred and mixed at 30°C for 60min, then heated to 80°C, stirred and reacted for 25h to obtain a light yellow suspension, filtered, and the obtained solid was washed with ethanol 6 times, and then vacuum dried at 50°C for 12h to obtain an intermediate product; 22.5g of the intermediate product was added to 200g of tetrahydrofuran, 15.1g of triethylamine was added, and stirred in an ice-water bath for 30min, 13.5g of acryloyl chloride was added, and the reaction was stirred in an ice-water bath for 60min, and then stirred at room temperature for 22h, filtered, and the filtered product was washed with tetrahydrofuran and acetone in sequence, and vacuum dried to obtain an N-halamine compound precursor;

[0065] Step B2, adding 115.8g of 4-aminobutane-1-thiol to 200g of ethanol, ultrasonically treating for 30min, then adding 16.1g of 4-pyridinecarboxaldehyde, stirring and reacting at 55°C for 10h, after the reaction is completed, distilling off the solvent under reduced pressure at 70°C to obtain a Schiff base-pyridine compound; adding 16.8g of the N-halamine compound precursor to 175g of ethanol, ultrasonically treating for 30min, heating to 65°C, then adding 0.3g of azobisisobutyronitrile and 13.6g of the Schiff base-pyridine compound, stirring and reacting for 4h, after the reaction is completed, filtering, washing the obtained solid with ethanol 4 times, and vacuum drying at 55°C to obtain a Schiff base-pyridine-halamine compound precursor;

[0066] 15.2 g of Schiff base-pyridine-halamine compound precursor and 13.9 g of tetradecane bromide were added to 200 g of dimethyl sulfoxide, and the mixture was reacted at 85° C. for 26 h. After the reaction was completed, the mixture was filtered, and the obtained solid product was washed with ethanol and dried to obtain a Schiff base-pyridine quaternary ammonium salt-halamine compound precursor;

[0067] Step B3, adding 2.9 g of boric acid and 3.5 g of melamine to 250 g of deionized water, heating to 105° C. and stirring at a speed of 300 r / min for 8 h, naturally cooling to room temperature, precipitating a crude product, filtering, and drying the obtained crude product at 75° C. for 25 h to obtain melamine diborate;

[0068] 3 g of nano copper powder, 0.3 g of melamine diborate, and 250 g of deionized water were mixed, stirred at a speed of 200 r / min, and heated at 250° C. until the deionized water was completely evaporated to obtain melamine diborate-coated copper powder, and the melamine diborate-coated copper powder was placed in a tube furnace, heated to 1000° C., and maintained for 3 h in an argon and hydrogen flow to obtain a modified copper powder, wherein the flow rate of argon was 200 sccm and the flow rate of hydrogen was 10 sccm;

[0069] The modified copper powder and 30wt% hydrogen peroxide aqueous solution were ultrasonically mixed at a mass ratio of 1:100 for 12.5h, reacted at 108°C for 22h, and after the reaction, hydroxylated modified copper powder was obtained. The hydroxylated modified copper powder, ethanol, and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane were mixed at a mass ratio of 17.5:55:2, stirred and reacted at 65°C for 45min in a light-proof environment and a nitrogen atmosphere, filtered, washed, and dried to obtain amino-modified copper powder;

[0070] The aminated copper powder and the graphene oxide powder were ultrasonically dispersed in deionized water to obtain an aminated copper powder dispersion and a graphene oxide dispersion with a concentration of 3.5 mg / mL; the aminated copper powder dispersion was added dropwise to the graphene oxide dispersion at a speed of 1.5 mL / min, stirred at a speed of 500 r / min for 10 min, and then ultrasonically treated at a power of 200 W for 10 min, and then ultrasonically treated in an ice water bath at a pH of 7.5 and an ultrasonic power of 60 W for 15 min, centrifuged, removed the supernatant, and dried to obtain a multi-component composite powder;

[0071] 3 g of the multi-component composite powder was dispersed in 45 mL of ethanol containing 5 wt% glutaraldehyde, reacted at 100° C. for 10 h, filtered, washed, and obtained a modified multi-component composite powder; 7.5 g of Schiff base-pyridine quaternary ammonium salt-halogenamine compound precursor was added to 110 g of dimethyl sulfoxide, and then 4 g of the modified multi-component composite powder was added, stirred and reacted at 50° C. for 13 h, filtered, washed, and dried to obtain an organic-inorganic composite material;

[0072] The organic-inorganic composite material was added into a 10 wt % sodium hypochlorite aqueous solution at a solid-liquid ratio of 1:30, and the pH was adjusted to 7 with acetic acid, stirred at room temperature for 2 h, filtered, washed, and dried to obtain a chlorinated organic-inorganic composite material.

[0073] Example 3

[0074] This embodiment discloses a method for preparing an antibacterial sunscreen composite fabric, comprising the following steps:

[0075] Step (1), mixing the recovered flax fiber with 1-butyl-3-methylimidazole acetate, stirring at a speed of 500 r / min in a constant temperature water bath at 75° C. for 1.5 h, adding dimethyl sulfoxide, continuing to stir for 2.5 h, then adding the chlorinated organic-inorganic composite material, stirring for 20 min, degassing at 40° C. for 10 h to obtain a spinning solution, spinning to obtain a cool antibacterial regenerated fiber; wherein the mass ratio of the recovered flax fiber, 1-butyl-3-methylimidazole acetate, dimethyl sulfoxide, and the chlorinated organic-inorganic composite material in the spinning solution is 1:18:54:0.5;

[0076] Step (2), blending cotton fiber and cool antibacterial regenerated fiber in a mass ratio of 60:40 into a yarn with a British count of 40S, knitting, and obtaining a yarn with a gram weight of 80g / m 2 The inner layer is immersed in a protective liquid, and after the immersion is completed, the inner layer is pre-baked and baked to obtain a modified inner layer; wherein the protective liquid is obtained by mixing polydimethylsiloxane, cyclohexane, and dual-doped carbon dots in a mass ratio of 8:92:0.5; the immersion conditions are: immersion at room temperature for 20 minutes, one immersion and one rolling, the rolling rate is 90%, and the bath ratio is 1:15;

[0077] Step (3), blending the modified polyester fiber and the cool antibacterial regenerated fiber in a mass ratio of 75:25 into a yarn with a British count of 60S, knitting, and obtaining a yarn with a gram weight of 100 g / m 2 The surface layer is immersed in a hydrophobic finishing agent, and after the immersion, pre-baked and baked to obtain a modified surface layer; wherein the hydrophobic finishing agent is obtained by mixing polydimethylsiloxane and isopropanol in a volume ratio of 10:25; the immersion conditions are: immersion at room temperature for 20 minutes, one immersion and one rolling, the rolling ratio is 75%, and the bath ratio is 1:15;

[0078] The modified inner layer and the modified surface layer are laminated, aligned and compounded to obtain an antibacterial and sun-proof composite fabric.

[0079] Example 4

[0080] This embodiment discloses a method for preparing an antibacterial sunscreen composite fabric, comprising the following steps:

[0081] Step (1), mixing the recovered flax fiber with 1-butyl-3-methylimidazole acetate, stirring at a speed of 600 r / min in a constant temperature water bath at 85° C. for 2.5 hours, adding dimethyl sulfoxide, continuing to stir for 3.5 hours, then adding the chlorinated organic-inorganic composite material, stirring for 40 minutes, degassing at 45° C. for 15 hours to obtain a spinning solution, spinning to obtain a cool antibacterial regenerated fiber; wherein the mass ratio of the recovered flax fiber, 1-butyl-3-methylimidazole acetate, dimethyl sulfoxide, and the chlorinated organic-inorganic composite material in the spinning solution is 1:22:66:0.7;

[0082] Step (2), blending cotton fiber and cool antibacterial regenerated fiber in a mass ratio of 70:30 into a yarn with a British count of 60S, knitting, and obtaining a yarn with a gram weight of 100 g / m 2 The inner layer is immersed in a protective liquid, and after the immersion is completed, the inner layer is pre-baked and baked to obtain a modified inner layer; wherein the protective liquid is obtained by mixing polydimethylsiloxane, cyclohexane, and dual-doped carbon dots in a mass ratio of 12:88:2; the immersion conditions are: immersion at room temperature for 30 minutes, one immersion and one rolling, the rolling rate is 95%, and the bath ratio is 1:25;

[0083] Step (3), blending the modified polyester fiber and the cool antibacterial regenerated fiber in a mass ratio of 85:15 into a yarn with a British count of 80S, knitting, and obtaining a yarn with a gram weight of 120 g / m 2 The surface layer is immersed in a hydrophobic finishing agent, and after the immersion, pre-baked and baked to obtain a modified surface layer; wherein the hydrophobic finishing agent is obtained by mixing polydimethylsiloxane and isopropanol in a volume ratio of 10:25; the immersion conditions are: immersion at room temperature for 30 minutes, one immersion and one rolling, the rolling rate is 88%, and the bath ratio is 1:25;

[0084] The modified inner layer and the modified surface layer are laminated, aligned and compounded to obtain an antibacterial and sun-proof composite fabric.

[0085] Example 5

[0086] This embodiment discloses a method for preparing an antibacterial sunscreen composite fabric, comprising the following steps:

[0087] Step (1), mixing the recovered flax fiber with 1-butyl-3-methylimidazole acetate, stirring at a speed of 550 r / min for 2 hours in a constant temperature water bath at 80° C., adding dimethyl sulfoxide, continuing to stir for 3 hours, then adding the chlorinated organic-inorganic composite material, stirring for 30 minutes, degassing at 40° C. for 12.5 hours to obtain a spinning solution, spinning to obtain a cool antibacterial regenerated fiber; wherein the mass ratio of the recovered flax fiber, 1-butyl-3-methylimidazole acetate, dimethyl sulfoxide, and the chlorinated organic-inorganic composite material in the spinning solution is 1:20:60:0.6;

[0088] Step (2), blending cotton fiber and cool antibacterial regenerated fiber in a mass ratio of 65:35 into a yarn with a British count of 50S, knitting, and obtaining a yarn with a gram weight of 90g / m 2 The inner layer is immersed in a protective liquid, and after the immersion is completed, the inner layer is pre-baked and baked to obtain a modified inner layer; wherein the protective liquid is obtained by mixing polydimethylsiloxane, cyclohexane, and dual-doped carbon dots in a mass ratio of 10:90:1.2; the immersion conditions are: immersion at room temperature for 25 minutes, one immersion and one rolling, the rolling rate is 93%, and the bath ratio is 1:20;

[0089] Step (3), blending the modified polyester fiber and the cool antibacterial regenerated fiber in a mass ratio of 80:20 into a yarn with a British count of 90S, knitting, and obtaining a yarn with a gram weight of 110 g / m 2 The surface layer is immersed in a hydrophobic finishing agent, and after the immersion, pre-baked and baked to obtain a modified surface layer; wherein the hydrophobic finishing agent is obtained by mixing polydimethylsiloxane and isopropanol in a volume ratio of 10:25; the immersion conditions are: immersion at room temperature for 25 minutes, one immersion and one rolling, the rolling rate is 81%, and the bath ratio is 1:20;

[0090] The modified inner layer and the modified surface layer are laminated, aligned and compounded to obtain an antibacterial and sun-proof composite fabric.

[0091] The modified polyester fiber and the chlorinated organic-inorganic composite material in the above Examples 3-5 are the modified polyester fiber prepared in Example 1 and the chlorinated organic-inorganic composite material prepared in Example 2, respectively.

[0092] Comparative Example 1

[0093] Comparative Example 1 Compared with Example 1, in the process of preparing the dual-doped carbon dots in Comparative Example 1, manganese sulfate monohydrate was not added, and other conditions remained unchanged.

[0094] Comparative Example 2

[0095] Comparative Example 2 Compared with Example 1, in the process of preparing the dual-doped carbon dots in Comparative Example 2, no titanium dioxide nanoparticles were added, and other conditions remained unchanged.

[0096] Comparative Example 3

[0097] Comparative Example 3 Compared with Example 1, in the process of preparing the modified polyester fiber in Comparative Example 3, amino-modified polyester fiber is used instead of protocatechuic aldehyde-modified polyester fiber, and other conditions remain unchanged.

[0098] Comparative Example 4

[0099] Comparative Example 4 Compared with Example 2, in the process of preparing the organic-inorganic composite material in Comparative Example 4, the Schiff base-pyridine-halogenamine compound precursor is used instead of the Schiff base-pyridine quaternary ammonium salt-halogenamine compound precursor, and other conditions remain unchanged.

[0100] Comparative Example 5

[0101] Comparative Example 5 Compared with Example 2, in the process of preparing the amino-modified copper powder, the nano copper powder was used instead of the hydroxylation-modified copper powder in Comparative Example 5, and other conditions remained unchanged.

[0102] Comparative Example 6

[0103] Comparative Example 6 Compared with Example 2, in the process of preparing the organic-inorganic composite material, the amino-modified copper powder is used instead of the multi-component composite powder in Comparative Example 6, and other conditions remain unchanged.

[0104] Comparative Example 7

[0105] Compared with Example 5, in the process of preparing the surface layer of Comparative Example 7, the modified polyester fiber prepared in Comparative Example 1 was used, and other conditions remained unchanged.

[0106] Comparative Example 8

[0107] Compared with Example 5, in Comparative Example 8, during the preparation of the surface layer, the modified polyester fiber prepared in Comparative Example 2 was used, and other conditions remained unchanged.

[0108] Comparative Example 9

[0109] Comparative Example 9 Compared with Example 5, in the process of preparing the surface layer of Comparative Example 9, protocatechuic aldehyde-modified polyester fiber is used instead of modified polyester fiber, and other conditions remain unchanged.

[0110] Comparative Example 10

[0111] Compared with Example 5, in Comparative Example 10, the modified polyester fiber prepared in Comparative Example 3 was used in the process of preparing the surface layer, and other conditions remained unchanged.

[0112] Comparative Example 11

[0113] Comparative Example 11 Compared with Example 5, in the process of producing cool antibacterial regenerated fiber, Comparative Example 11 adopts the chlorinated organic-inorganic composite material prepared in Comparative Example 4, while other conditions remain unchanged.

[0114] Comparative Example 12

[0115] Comparative Example 12 is compared with Example 5. In the process of producing the cool antibacterial regenerated fiber, Comparative Example 12 uses the chlorinated organic-inorganic composite material prepared in Comparative Example 5, while other conditions remain unchanged.

[0116] Comparative Example 13

[0117] Comparative Example 13 is compared with Example 5. In the process of producing the cool antibacterial regenerated fiber, Comparative Example 13 uses the chlorinated organic-inorganic composite material prepared in Comparative Example 6, while other conditions remain unchanged.

[0118] In the above embodiments and comparative examples, graphene oxide powder, purity: 99%, flake diameter: >5μm, article number: 133423, brand: Kramar, comes from Shanghai Ziyi Reagent Factory; nano copper powder, microscopic morphology is spherical, average particle size is 100nm, article number is LF-Cu-N100, comes from Qinghe County Chaotai Metal Materials Co., Ltd.; recycled flax fiber is recycled flax fiber after degumming treatment, comes from Hangzhou Shanglu Silk Co., Ltd.; titanium dioxide nanoparticles are high-purity anatase type, with a particle size of 10-20nm, and come from Qinghe County Chaotai Metal Materials Co., Ltd.

[0119] Experimental example

[0120] Test 1: Performance tests were performed on the antibacterial and sun-proof composite fabrics prepared in Examples 3-5 and Comparative Examples 7-13.

[0121] 1. Antibacterial performance test: According to GB / T 20944.3-2008, the antibacterial effect of each group of fabric samples on Escherichia coli and Staphylococcus aureus was tested after washing 100 times.

[0122] 2. Sun protection performance test: Refer to GB / T 18830-2009 for UPF (ultraviolet protection factor) test, sample size 5cm×5cm.

[0123] 3. Contact coolness coefficient: refer to GB / T 35263-2017 for testing. The sample platform temperature is 20℃, the heat detection plate temperature is 35℃, and the contact coolness coefficient is tested by a contact warm and cold tester.

[0124] The test results are shown in Table 1:

[0125] Table 1

[0126]

[0127] It can be seen from the test results in Table 1 that the antibacterial and sunscreen composite fabrics prepared in Examples 3-5 of the present invention have excellent long-lasting antibacterial properties, sunscreen properties, and thermal conductivity and coolness. From the comparison of Comparative Examples 7-8 with Example 5, it can be seen that the doping of nano-titanium dioxide and manganese in the dual-doped carbon dots improves the antibacterial effect of the carbon dots by promoting the generation of active oxygen, and the doping of nano-titanium dioxide can improve the ultraviolet shielding efficiency of the carbon dots. Therefore, the dual-doped carbon dots are grafted on the polyester fibers to obtain surface-modified polyester fibers, which can improve the antibacterial and sunscreen properties of the polyester fibers. From the comparison of Comparative Examples 9-10 with Example 5, it can be seen that protocatechuic aldehyde is connected to the surface-modified polyester fibers and chelated with iron ions. The protocatechuic aldehyde structure has excellent antibacterial and ultraviolet absorption capabilities due to its own benzene ring and phenolic hydroxyl groups. The chelation of iron ions can enhance the adsorption of bacteria and improve the antibacterial effect on the one hand, and on the other hand, iron ions can increase the reflection and scattering of ultraviolet rays on the surface of the polyester fiber and improve the sunscreen effect; From the comparison of Comparative Example 11 with Example 5, It can be seen that the quaternary ammonium salt in the chlorinated organic-inorganic composite material attracts bacteria to the N-halamine site through electrostatic attraction, quickly killing it, thereby effectively improving its antibacterial activity and improving the antibacterial performance of the fabric; from the comparison of Comparative Example 12 and Example 5, it can be seen that the boron nitride coating avoids the oxidation of the nano copper powder, so that it maintains a stable antibacterial performance, and the modified copper powder has better thermal conductivity than the copper powder, thereby improving the contact coolness coefficient and antibacterial property of the fabric; from the comparison of Comparative Example 13 and Example 5, it can be seen that the modified copper powder is deposited on the graphene oxide nanosheets with thermal conductivity and antibacterial properties to form a heat conduction channel with "points and surfaces", and the combination of the modified copper powder and graphene oxide is conducive to establishing a heat conduction path, and a multi-component composite powder with high thermal conductivity efficiency and antibacterial rate is obtained, thereby improving the contact coolness coefficient and antibacterial property of the fabric.

[0128] Test 2: The antibacterial and sun-proof composite fabrics prepared in Examples 3-5 were tested for hydrophobicity and softness.

[0129] 1. Hydrophobicity test: Use a 4μL water droplet to test the water contact angle through a water contact angle meter;

[0130] 2. Softness test: Use The system conducts hand property tests with a sampling frequency of 10 times per second. The test samples are circular with an area of ​​approximately 100 square meters. They comply with the T / ZFB 003-2019 standard and score the softness of each group of fabrics.

[0131] The test results are shown in Table 2:

[0132] Table 2

[0133] Water contact angle / ° Softness score / points Example 3 163.6 74.84±0.22 Example 4 165.2 75.26±0.29 Example 5 164.4 75.92±0.26

[0134] It can be seen from the test results in Table 2 that the antibacterial and sun-proof composite fabrics prepared in Examples 3-5 of the present invention have both good hydrophobicity and antifouling properties and softness.

[0135] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an antibacterial sunscreen composite fabric, characterized in that: The following steps are involved: Step (1), using recycled flax fiber, 1-butyl-3-methylimidazole acetate, and chlorinated organic-inorganic composite material as raw materials to prepare spinning solution, spinning, and obtaining cool antibacterial regenerated fiber; wherein the preparation method of the chlorinated organic-inorganic composite material comprises the following steps: Step B1, guanidine carbonate reacts with α-acetyl-γ-butyrolactone to obtain an intermediate product; the intermediate product reacts with acryloyl chloride to obtain an N-halamine compound precursor; Step B2, 4-aminobutane-1-thiol reacts with 4-pyridinecarboxaldehyde to obtain a Schiff base-pyridine compound, which is then reacted with an N-halamine compound precursor, and finally subjected to a quaternization reaction to obtain a Schiff base-pyridine quaternary ammonium salt-halamine compound precursor; Step B3, using boric acid and melamine as raw materials to prepare melamine diborate, coating the nano copper powder with melamine diborate, and then calcining to obtain modified copper powder; treating the modified copper powder to obtain amino modified copper powder; The aminated modified copper powder and graphene oxide are assembled to obtain a multi-component composite powder; the multi-component composite powder is combined with a Schiff base-pyridine quaternary ammonium salt-halogenamine compound precursor using glutaraldehyde as a crosslinking agent to obtain an organic-inorganic composite material, which is then treated with sodium hypochlorite to obtain a chlorinated organic-inorganic composite material; Step (2), blending cotton fiber and cool antibacterial regenerated fiber into yarn, knitting, and obtaining an inner layer; immersing the inner layer in a protective liquid, and after the immersion is completed, pre-baking and baking to obtain a modified inner layer; Step (3), blending the modified polyester fiber and the cool antibacterial regenerated fiber into yarn, knitting, and obtaining a surface layer; immersing the surface layer in a hydrophobic finishing agent, and after the immersion is completed, pre-baking and baking to obtain a modified surface layer; The modified inner layer and the modified surface layer are laminated, aligned and compounded to obtain an antibacterial and sun-proof composite fabric.

2. The method for preparing the antibacterial sunscreen composite fabric according to claim 1, characterized in that: In the step (1), the preparation method of the cool antibacterial regenerated fiber is as follows: the recycled flax fiber is mixed with 1-butyl-3-methylimidazole acetate, stirred at a speed of 500-600r / min for 1.5-2.5h in a constant temperature water bath at 75-85°C, dimethyl sulfoxide is added, stirring is continued for 2.5-3.5h, and then the chlorinated organic-inorganic composite material is added, stirred for 20-40min, degassed at 35-45°C for 10-15h to obtain a spinning solution, and spinning is performed; wherein the mass ratio of the recycled flax fiber, 1-butyl-3-methylimidazole acetate, dimethyl sulfoxide, and the chlorinated organic-inorganic composite material in the spinning solution is 1:(18-22):(54-66):(0.5-0.7).

3. The method for preparing the antibacterial sunscreen composite fabric according to claim 1, characterized in that: In the step (1), the preparation method of the chlorinated organic-inorganic composite material is: Step B1, guanidine carbonate, α-acetyl-γ-butyrolactone, triethylamine, and ethanol are mixed in a mass ratio of (11.3-22.6):(2.4-4.8):(3.8-7.6):(23-46), stirred at 28-32°C for 40-80min, then heated to 75-85°C, stirred for reaction for 20-30h to obtain a light yellow suspension, filtered, washed, and dried to obtain an intermediate product; the intermediate product is added with tetrahydrofuran Add triethylamine to furan, stir in an ice-water bath for 20-40 minutes, add acryloyl chloride, stir in an ice-water bath for 50-70 minutes, then stir at room temperature for 20-24 hours, filter, wash, and vacuum dry to obtain an N-halamine compound precursor; wherein the mass ratio of the intermediate product, tetrahydrofuran, triethylamine, and acryloyl chloride is (15-30):(150-250):(10.1-20.1):(9-18); Step B2, adding 4-aminobutane-1-thiol to ethanol, ultrasonically treating for 20-40 min, then adding 4-pyridinecarboxaldehyde, stirring and reacting at 50-60° C. for 8-12 h, after the reaction is completed, removing the solvent by distillation under reduced pressure to obtain a Schiff base-pyridine compound; wherein the mass ratio of 4-aminobutane-1-thiol, ethanol, and 4-pyridinecarboxaldehyde is (10.5-21):(150-250):(10.7-21.4); Add the N-halamine compound precursor to ethanol, perform ultrasonic treatment for 20-40 minutes, heat to 50-80°C, then add azobisisobutyronitrile and Schiff base-pyridine compound, stir and react for 3-5 hours, filter, wash and dry after the reaction to obtain Schiff base-pyridine-halamine compound precursor; wherein the mass ratio of N-halamine compound precursor, ethanol, azobisisobutyronitrile and Schiff base-pyridine compound is (11.2-22.4):(150-200):(0.2-0.5):(9.7-19.4); Add dimethyl sulfoxide to a Schiff base-pyridine-halogenamine compound precursor and tetradecane bromide in a mass ratio of (10.2-20.2):(10.4-17.3):(150-250), react at 80-90° C. for 24-30 hours, filter, wash, and dry after the reaction to obtain a Schiff base-pyridine quaternary ammonium salt-halogenamine compound precursor; Step B3, mixing boric acid, melamine and deionized water in a mass ratio of (1.9-3.8):(2.5-4.5):(200-300), heating to 100-110° C. and stirring at a speed of 200-400 r / min for 7-9 hours, cooling naturally to room temperature, precipitating a crude product, filtering and drying to obtain melamine diborate; Mixing nano copper powder, melamine diborate and deionized water in a mass ratio of (2-4):(0.2-0.4):(200-300), stirring at a speed of 150-250 r / min, heating at 240-260° C. until the deionized water is completely evaporated to obtain melamine diborate-coated copper powder, heating the melamine diborate-coated copper powder to 900-1100° C., maintaining the mixture in an argon and hydrogen flow for 2.5-3.5 hours to obtain modified copper powder, wherein the flow rate of argon is 200 sccm and the flow rate of hydrogen is 10 sccm; The modified copper powder and 30wt% hydrogen peroxide aqueous solution are ultrasonically mixed at a mass ratio of 1:100 for 10-15h, and reacted at 105-110°C for 20-24h. After the reaction is completed, a hydroxylated modified copper powder is obtained. The hydroxylated modified copper powder, ethanol, and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane are mixed at a mass ratio of (15-20):(50-60):(1.5-2.5), and stirred at 60-70°C for 30-60min in a light-proof environment and a nitrogen atmosphere, and filtered, washed, and dried to obtain an amino-modified copper powder; The aminated copper powder and the graphene oxide powder were ultrasonically dispersed in deionized water to obtain an aminated copper powder dispersion and a graphene oxide dispersion with a concentration of 2-5 mg / mL; the aminated copper powder dispersion was added dropwise to the graphene oxide dispersion at a speed of 1-2 mL / min, stirred at a speed of 400-600 r / min for 5-15 min, and then ultrasonically treated at a power of 150-250 W for 5-15 min, and then ultrasonically treated in an ice water bath at a pH of 7-8 and an ultrasonic power of 50-70 W for 10-20 min, centrifuged, removed the supernatant, and dried to obtain a multi-component composite powder; The multi-component composite powder is mixed with ethanol containing 5 wt% glutaraldehyde in a dosage ratio of (2-4) g: (30-60) mL, reacted at 95-105° C. for 8-12 h, filtered, washed, and obtained a modified multi-component composite powder; the Schiff base-pyridine quaternary ammonium salt-halogenamine compound precursor, dimethyl sulfoxide, and the modified multi-component composite powder are mixed in a mass ratio of (5-10): (100-120): (3-5), stirred and reacted at 45-55° C. for 10-16 h, filtered, washed, and dried to obtain an organic-inorganic composite material; The organic-inorganic composite material is added to a 10wt% sodium hypochlorite aqueous solution at a solid-liquid ratio of 1:(25-35), and the pH is adjusted to 7 with acetic acid, stirred at room temperature for 1.5-2.5h, filtered, washed, and dried to obtain a chlorinated organic-inorganic composite material.

4. The method for preparing the antibacterial sunscreen composite fabric according to claim 1, characterized in that: In the step (2), the mass ratio of the cotton fiber to the cool antibacterial regenerated fiber is (60-70):(30-40), the English count of the blended yarn is 40-60S, and the gram weight of the inner layer is 80-100g / m 2 The protective liquid is obtained by mixing polydimethylsiloxane, cyclohexane and dual-doped carbon dots in a mass ratio of (8-12):(88-92):(0.5-2).

5. The method for preparing the antibacterial sunscreen composite fabric according to claim 1, characterized in that: In the step (2), the immersion conditions are: immersion at room temperature for 20-30 minutes, immersion and rolling, the rolling rate is 90-95%, and the bath ratio is 1:(15-25).

6. The method for preparing the antibacterial sunscreen composite fabric according to claim 1, characterized in that: In the step (3), the mass ratio of the modified polyester fiber and the cool antibacterial regenerated fiber is (75-85):(15-25), the English count of the blended yarn is 60-80S; the gram weight of the surface layer is 100-120g / m 2 ; The hydrophobic finishing agent is obtained by mixing polydimethylsiloxane and isopropyl alcohol in a volume ratio of 10:

25.

7. The method for preparing the antibacterial sunscreen composite fabric according to claim 1, characterized in that: In the step (3), the immersion conditions are: immersion at room temperature for 20-30 minutes, immersion and rolling, the rolling rate is 75-88%, and the bath ratio is 1:(15-25).

8. The method for preparing the antibacterial sunscreen composite fabric according to claim 1, characterized in that: In the step (3), the method for preparing the modified polyester fiber comprises the following steps: Step A1, wash freshly picked guava leaves with water and then dry them, grind them to obtain guava leaf powder, mix the guava leaf powder with deionized water, boil them at 90-95°C for 4.5-5.5h, filter them, heat them at 65-75°C to concentrate the filtrate to 5-10mL, add manganese sulfate monohydrate and titanium dioxide nanoparticles, keep them at 180-190°C for 5-6h, filter them, and dry them to obtain dual-doped carbon dots; wherein the mass ratio of guava leaf powder, deionized water, manganese sulfate monohydrate, and titanium dioxide nanoparticles is (15-20):(60-80):(0.03-0.06):(0.05-0.08); The dual-doped carbon dots, activated polyester fibers, p-toluenesulfonic acid, and cyclohexane are mixed in a mass ratio of (1-2): (10-15): (0.1-0.2): (150-200), stirred and reacted at 120-140° C. for 3-5 hours in a nitrogen atmosphere, and after the reaction is completed, filtered, washed, and dried to obtain a surface-modified polyester fiber; Step A2, 3-aminopropyltriethoxysilane and ethanol are mixed in a ratio of (8-16) g: (20-50) mL, and acetic acid is added to adjust the pH to 3.8-4.2 to obtain a mixed solution; the surface-modified polyester fiber is added to the mixed solution in a solid-liquid ratio of 1: (15-25), immersed at 65-75° C. for 40-80 min, taken out, washed, and dried to obtain an amino-modified polyester fiber; Protocatechuic aldehyde is added to deionized water to dissolve to obtain a treatment solution with a concentration of 5-8 mg / mL. Amino-modified polyester fiber is first added to the treatment solution at a solid-to-liquid ratio of 1:(10-20), stirred at 45-55° C. for 10-15 hours, taken out, dried at 55-65° C. for 50-70 minutes, washed, and obtained protocatechuic aldehyde-modified polyester fiber; at 75-85° C., the protocatechuic aldehyde-modified polyester fiber is soaked in a 0.2 mol / L ferric chloride aqueous solution at a solid-to-liquid ratio of 1:(10-20) for 1-2 hours, taken out, dried at 55-65° C. for 50-70 minutes, washed, and dried to obtain a modified polyester fiber.

9. The method for preparing the antibacterial sunscreen composite fabric according to claim 8, characterized in that: In the step (3), the preparation method of the activated polyester fiber is as follows: immersing the polyester fiber in a sodium hydroxide aqueous solution with a concentration of 20 g / L, alkali immersion treatment at 90-100° C. for 20-40 min, transferring it into a deionized water mixture of choline chloride and oxalic acid, deep treatment at 40-80° C. for 0.5-2 h, washing, and drying to obtain the activated polyester fiber, wherein the mass ratio of choline chloride to oxalic acid in the deionized water mixture of choline chloride and oxalic acid is 3:2, the total concentration of choline chloride and oxalic acid is 50 g / L, and the bath ratios of the alkali immersion treatment and the deep treatment are both (25-35):

1.

10. An antibacterial sunscreen composite fabric prepared by the method for preparing an antibacterial sunscreen composite fabric according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A kind of preparation method of highly breathable antibacterial functional composite fabric

    CN106515152B

  • Cool-feeling breathable fabric for sunscreen clothes and preparation method of cool-feeling breathable fabric

    CN117382267A

  • Antibacterial moisture-permeable multilayer composite fabric and preparation method thereof

    CN117656619A

  • Antibacterial breathable knitted fabric and preparation method thereof

    CN118560124A

  • Regenerated antibacterial sunscreen sportswear fabric

    CN219686750U